Cilengitide, an αvβ3-integrin inhibitor, enhances the efficacy of anti-programmed cell death-1 therapy in a murine melanoma model. Issue 2 (1st February 2022) - Pan, Xin; Yi, Minxiao; Liu, Chaofan; Jin, Yu; Liu, Bo; Hu, Guangyuan; Yuan, Xianglin
ABSTRACT: Integrins play an important role in multiple stages of tumor progression and metastasis. Previous studies have shown synergistic effects of combined αvβ6-integrin and αvβ8-integrin inhibitors with immunotherapy. However, the role of αvβ3-integrin inhibitor in tumor immunity is still unclear. In this study, we aimed to elucidate the impact of the αvβ3-integrin inhibitor on PD-L1 expression and sensitivity to immune checkpoint blockade in melanoma. We investigated the effects of cilengitide, an αvβ3-integrin inhibitor, on cell viability and apoptosis of melanoma cell lines. And we explored how cilengitide regulated the expression of PD-L1 in melanoma cells in vitro and in vivo, using immunofluorescence, flow cytometry, Western blotting, and immunohistochemistry. A subcutaneous B16 murine melanoma model was utilized to determine whether combining cilengitide with anti-PD1 therapy inhibited tumor growth and positively regulated tumor microenvironment (TME). Our results showed that cilengitide inhibited cell viability and induced apoptosis in B16 and A375 cell lines. Furthermore, cilengitide decreased PD-L1 expression by reducing STAT3 phosphorylation in two melanoma cell lines. Cilengitide also reduced subcutaneous tumor PD-L1 expression in the B16 murine melanoma model. Accordingly, cilengitide positively regulated antitumor immune responses and provided durable therapy when combined with anti-PD1 monoclonal antibody in the murine melanoma model. This combination therapy reduced tumor growth and extended survival. Our study highlights that cilengitide enhances the efficacy of anti-PD1 therapy and produces a stronger antitumor immune response. This combination therefore represents a novel therapeutic regimen that may improve immunotherapy treratment. GRAPHICAL ABSTRACT: uf0001